Atomic scale modeling of iron-doped biphasic calcium phosphate bioceramics. (1st March 2017) - Gomes, Sandrine; Kaur, Amandeep; Grenèche, Jean-Marc; Nedelec, Jean-Marie; Renaudin, Guillaume
Graphical abstract: Abstract: Biphasic calcium phosphates (BCPs) are bioceramics composed of hydroxyapatite (HAp, Ca10 (PO4 )6 (OH)2 ) and beta-Tricalcium Phosphate (β-TCP, Ca3 (PO4 )2 ). Because their chemical and mineral composition closely resembles that of the mineral component of bone, they are potentially interesting candidates for bone repair surgery, and doping can advantageously be used to improve their biological behavior. However, it is important to describe the doping mechanism of BCP thoroughly in order to be able to master its synthesis and then to fully appraise the benefit of the doping process. In the present paper we describe the ferric doping mechanism: the crystallographic description of our samples, sintered at between 500 °C and 1100 °C, was provided by Rietveld analyses on X-ray powder diffraction, and the results were confirmed using X-ray absorption spectroscopy and 57 Fe Mössbauer spectrometry. The mechanism is temperature-dependent, like the previously reported zinc doping mechanism. Doping was performed on the HAp phase, at high temperature only, by an insertion mechanism. The Fe 3+ interstitial site is located in the HAp hexagonal channel, shifted from its centre to form a triangular three-fold coordination. At lower temperatures, the Fe 3+ are located at the centre of the channel, forming linear two-fold coordinated O-Fe-O entities. The knowledge of the doping mechanism is a prerequisite for a correct synthesis of the targeted bioceramic with the adapted (Ca + Fe)/P ratio, and so to be able to correctly predict its potential iron release or magnetic properties. Statement of Significance: Biphasic calcium phosphates (BCPs) are bioceramics composed of hydroxyapatite (HAp, Ca10 (PO4 )6 (OH)2 ) and beta-Tricalium Phosphate (β-TCP, Ca3 (PO4 )2 ). Because their chemical and mineral composition closely resembles that of the mineral component of bone, they are potentially interesting candidates for bone repair surgery. Doping can advantageously be used to improve their biological behaviors and/or magnetic properties; however, it is important to describe the doping mechanism of BCP thoroughly in order to fully appraise the benefit of the doping process. The present paper scrutinizes in detail the incorporation of ferric cation in order to correctly interpret the behavior of the iron-doped bioceramic in biological fluid. The temperature dependent mechanism has been fully described for the first time. And it clearly appears that temperature can be used to design the doping according to desired medical application: blood compatibility, remineralization, bactericidal or magnetic response.